2018
DOI: 10.3390/cryst8010040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MnO2 Concentration on the Conductivity of Ce0.9Gd0.1MnxO2−δ

Abstract: Samples with the composition Ce 0.9 Gd 0.1 Mn x O 2−δ with x = 0.01, 0.02, and 0.05 Mn-addition were prepared by mixed oxide route from Ce 0.9 Gd 0.1 O 2−δ and MnO 2 and sintered at 1300 • C. The electronic conductivity was measured using a modified Hebb-Wagner technique, the electrical conductivity was investigated by impedance spectroscopy, and oxygen permeation was measured for the sample with x = 0.05. An increase of the electronic partial conductivity with increasing Mn addition was observed, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…An extended description of the microcontact measurement method can be found in previous publications. 24,[63][64][65] Measurements were executed at temperatures between 800-400…”
Section: Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…An extended description of the microcontact measurement method can be found in previous publications. 24,[63][64][65] Measurements were executed at temperatures between 800-400…”
Section: Compositionmentioning
confidence: 99%
“…30,46 In case of Mn, simulations and measurements showed that the increased electronic partial conductivity with increasing Mn addition can be attributed to an additional Mn 3d-related state between the top of the valence band and the bottom of the Ce 4f band. 24,29 Also Khare et al observed the development of an additional feature at the binding energy position of 2.6 eV in the valence band of CeO 2 after doping with 2-6 mol% iron. 47 This feature is related to the introduction of an additional Fe-d level which can work as a "stepping stone" for electrons within the broad ceria bandgap.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Proton conductivity may be observed in acceptor-doped perovskite oxides such as Ba 0.9 La 0.1 Zr 0.25 Sn 0.25 In 0.5 O 3−a , as studied by Skubida et al [2], and terbium-substituted lanthanum orthoniobate [3]. Oxygen ions are mobile charge carriers in materials such as substituted bismuth vanadate [4] and doped cerium oxide [5,6], as studied by Ring and Fuierer, and to a minor extent and at high temperature, they are also mobile charge carriers in ceramic proton conductors. Fluorine ions, the first mobile ions studied in solid-state ionic conductors, are present in SrF 2 -YF 3 solid solutions, as reported by Breuer et al [7].…”
mentioning
confidence: 95%